Editorial - Noor, Noraini M. (IIUM Press, 2010)
Development and progress are essential to achieving higher standards of living and enhanced quality of life. Muslim countries, after independence, have aspired and struggled for development and a decent life without fully comprehending the underlying rationale that formed the basis for this striving. It would be instructive, therefore, to reflect on Martin Lings' explanation of the concepts of "development" (tatawwur), "progress" (taqaddum), "renewal" (tajdid) and "renaissance" (nahdah).....